2019
DOI: 10.1097/md.0000000000014070
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of 2887 patients with hepatocellular carcinoma

Abstract: This study was aimed to estimate the survival rate characteristics of 2887 hepatocellular carcinoma (HCC) patients in the single-center and identify useful prognostic factors to help in the clinical management of patients with HCC. Two thousand eight hundred eighty-seven patients diagnosed with HCC at the Fourth Hospital of Hebei Medical University, China, between January 2002 and December 2015 were involved. The causes and baseline characteristics were summarized. Median survival time wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 18 publications
9
54
3
3
Order By: Relevance
“…Further, univariate analysis employing clinical factors of patients found that tumor stage of patients can act as a strong prognostic factor in the various types of survival, i.e., OS, RFS/DFS, PFS, and DSS of patients. Eventually, the multivariate survival analysis revealed the tumor stage as a sole independent prognostic factor, which was also corroborated with the previous literature (Aino et al, 2014;Wang and Li, 2019). The correct tumor stage identification is quite a tedious and challenging task in comparison to the quantification of the expression of genes.…”
Section: Discussionsupporting
confidence: 86%
“…Further, univariate analysis employing clinical factors of patients found that tumor stage of patients can act as a strong prognostic factor in the various types of survival, i.e., OS, RFS/DFS, PFS, and DSS of patients. Eventually, the multivariate survival analysis revealed the tumor stage as a sole independent prognostic factor, which was also corroborated with the previous literature (Aino et al, 2014;Wang and Li, 2019). The correct tumor stage identification is quite a tedious and challenging task in comparison to the quantification of the expression of genes.…”
Section: Discussionsupporting
confidence: 86%
“…It is therefore crucial to enable access to HBV viral load monitoring and antiviral treatment to HBV-infected patients as it might prevent a significant proportion of HCC; HCV was also found as an important etiology of HCC in our study, therefore, efforts to prevent unsafe injection could potentially play an important role in the prevention of HCC. In our context of delayed consultation, survival was poorer compared to the results of Wang et al [25] who found a survival of 49.3% and 35.3% in 1 and 2 years respectively. In our work, we showed that the prognostic factors were the BCLC stage, the degree of hepatocellular insufficiency as in Asian studies [25] [26].…”
Section: Discussioncontrasting
confidence: 83%
“…In our context of delayed consultation, survival was poorer compared to the results of Wang et al [25] who found a survival of 49.3% and 35.3% in 1 and 2 years respectively. In our work, we showed that the prognostic factors were the BCLC stage, the degree of hepatocellular insufficiency as in Asian studies [25] [26].…”
Section: Discussioncontrasting
confidence: 83%
“…Advanced age has been widely reported to be associated with poor survival outcomes in HCC, regardless of the staging or therapeutic modes [28,29], but has never been explored in patients with HCC with spinal metastases. Previous studies used a variety of age cut points, ranging from 60 to 70 years old [27][28][29][30]. Our study is the rst one to demonstrate the effect of old age (> 60 years) on the survival of patients with HCC-derived spinal metastases.…”
Section: Discussionmentioning
confidence: 86%